2014
DOI: 10.1103/physrevb.89.081107
|View full text |Cite
|
Sign up to set email alerts
|

Typical medium dynamical cluster approximation for the study of Anderson localization in three dimensions

Abstract: We develop a systematic typical medium dynamical cluster approximation that provides a proper description of the Anderson localization transition in three dimensions (3D). Our method successfully captures the localization phenomenon both in the low and large disorder regimes, and allows us to study the localization in different momenta cells, which renders the discovery that the Anderson localization transition occurs in a cell-selective fashion. As a function of cluster size, our method systematically recover… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
96
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(105 citation statements)
references
References 41 publications
(81 reference statements)
8
96
1
Order By: Relevance
“…35 In Ref. 35 we confirmed that the typical density of states vanishes for states which are localized and it is finite for extended states.…”
Section: B Typical Medium Theory With Off-diagonal Disordersupporting
confidence: 48%
See 4 more Smart Citations
“…35 In Ref. 35 we confirmed that the typical density of states vanishes for states which are localized and it is finite for extended states.…”
Section: B Typical Medium Theory With Off-diagonal Disordersupporting
confidence: 48%
“…To include the effects of off-diagonal disorder, Gonis 27 extended the Molecular CPA, which uses a selfconsistently embedded finite size cluster to capture nonlocal corrections to the CPA. However, he criticized the MCPA for violating translational invariance and other critical properties of a valid quantum cluster theory 15,35 . In order to take into account such non-local effects on offdiagonal disorder models while maintaining translational invariance, we extend the BEB formalism using the DCA scheme [29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations